New data on the morphology and systematic status of Spinitectus petrowi and Spinitectus gigi (Nematoda: Cystidicolidae) parasitic in catfishes in central China - Moravec, Frantisek; Nie, Pin; Wang, Guitang (Folia parasitologica, 2004)
Two little-known nematode species of the genus Spinitectus Fourment, 1883, S. petrowi Belous, 1965 (prevalence 25%, intensity 1-8) and S. gigi Fujita, 1927 (prevalence 10%, intensity 2-3), were collected from the gastrointestinal tract of the yellow catfish, Pelteobagrus fulvidraco (Richardson), from Liangzihu Lake, Hubei Province, central China, in September of 2002. The light and scanning electron microscopical examination of this material, supplemented by a few museum specimens of S. gigi collected from the catfish Clariasfuscus (Lacépède) in southern China, made it possible to study in detail the morphology of these parasite species and to redescribe them. The first species, whose correct name is S. petrowi Belous, 1965, exhibits some morphological features (e.g., unusually short vestibule, shape of pseudolabia and of the left spicule) not found in most other congeners; a unique feature is the presence of peculiar pairs of transversely oriented peg-like cuticular spines with rounded ends on the ventral surface of the female tail. Spinitectus gigi was found to have 28-31 cuticular spines in the first ring, relatively long distances between the 2nd-7th rings of spines, and anterior rings divided into 2 sectors; the excretory pore is located at the level of the 4th ring of cuticular spines; males posses 4 pairs of preanal- and 6 pairs of postanal caudal papillae and a pair of small phasmids. Spinitectus bagri Wang, Wu et Yu, 1993 and S. wulingensis Yu et Wang, 1997 are considered junior synonyms of S. petrowi, whereas S. clariasi Ky, 1971, S. ophicephali Ky, 1971 and S. yuanjiangensis Wang, Wu et Yu, 1997 are regarded to be junior synonyms of S. gigi. Spinitectus petrowi was not previously reported from China.
Keywords: Čína; Nematoda; gastrointestinální trakt; hlístice; Animals; mužské pohlaví; Gastrointestinal Tract; Microscopy, Electron, Scanning; ženské pohlaví; zvířata; Catfishes; China; Female; sumci; Male; mikroskopie elektronová rastrovací